Real-life experience with ceftobiprole in Canada: Results from the CLEAR (CanadianLEadership onAntimicrobialReal-life usage) registry. (March 2021) - Zhanel, George G.; Kosar, Justin; Baxter, Melanie; Dhami, Rita; Borgia, Sergio; Irfan, Neal; MacDonald, Kelly S.; Dow, Gordon; Lagacé-Wiens, Philippe; Dube, Maxime; Bergevin, Marco; Tascini, Carlo; et al.
Highlights: Use of ceftobiprole in Canadian patients using data captured by the CLEAR registry. Ceftobiprole is used as directed therapy to treat a variety of severe infections caused by MRSA. Ceftobiprole is primarily used in patients failing previous antimicrobials. Ceftobiprole is frequently added to, and thus used in combination with, daptomycin or vancomycin. Ceftobiprole shows high microbiological and clinical cure rates along with an excellent safety profile. Abstract: Objectives: Ceftobiprole is an advanced-generation cephalosporin with a favourable safety profile. Published data on the clinical use of ceftobiprole are limited. We report use of ceftobiprole in Canadian patients using data captured by the CLEAR registry. Methods: The CLEAR registry uses the web-based research data management program REDCap™ (online survey) to facilitate clinicians entering details associated with their clinical experiences using ceftobiprole. Results: Data were available for 38 patients treated with ceftobiprole. The most common infections treated were endocarditis (42.1% of patients), bone and joint infection (23.7%) and hospital-associated bacterial pneumonia (15.8%). 92.1% of patients had bacteraemia and 21.1% were in intensive care. Ceftobiprole was used because of failure of (71.1%), resistance to (18.4%) or adverse effects from (10.5%) previously prescribed antimicrobial agents. Ceftobiprole was primarily used as directed therapy for methicillin-resistant Staphylococcus aureus (MRSA) infections (94.7% of patients). Ceftobiprole susceptibility testing was performed on isolates from 47.4% of patients. It was used concomitantly with daptomycin in 55.3% of patients and with vancomycin in 18.4% of patients. Treatment duration was primarily >10 days (65.8% of patients) with microbiological success in 97.0% and clinical success in 84.8% of patients. 2.6% of patients had gastrointestinal adverse effects. Conclusion: In Canada to date, ceftobiprole is used as directed therapy to treat a variety of severe infections caused by MRSA. It is primarily used in patients failing previous antimicrobials, is frequently added to, and thus used in combination with daptomycin or vancomycin with high microbiological and clinical cure rates and an excellent safety profile.